Biophysical and modeling-based approach for the identification of inhibitors against DOHH from Leishmania donovani. (9th July 2022) - Katiki, Madhusudhanarao; Sharma, Monica; Neetu, Neetu; Rentala, Madhubala; Kumar, Pravindra
Abstract: The amino acid hypusine (N ε -4-amino-2-hydroxybutyl(lysine)) occurs only in isoforms of eukaryotic translation factor 5A (eIF5A) and has a role in initiating protein translation. Hypusinated eIF5A promotes translation and modulates mitochondrial function and oxygen consumption rates. The hypusination of eIF5A involves two enzymes, deoxyhypusine synthase and deoxyhypusine hydroxylase (DOHH). DOHH is the second enzyme that completes the synthesis of hypusine and the maturation of eIF5A. Our current study aims to identify inhibitors against DOHH from Leishmania donovani ( Ld DOHH), an intracellular protozoan parasite causing Leishmaniasis in humans. The Ld DOHH protein was produced heterologously in Escherichia coli BL21(DE3) cells and characterized biochemically. The three-dimensional structure was predicted, and the compounds folic acid, scutellarin and homoarbutin were selected as top hits in virtual screening. These compounds were observed to bind in the active site of Ld DOHH stabilizing the structure by making hydrogen bonds in the active site, as observed by the docking and molecular dynamics simulation studies. These results pave the path for further investigation of these molecules for their anti-leishmanial activities.